FACTOR ANALYSIS OF THE CAUSES OF UNSATISFACTORY OUTCOMES IN THE PERINATAL PERIOD IN WOMEN INFECTED WITH COVID-19 (Conferencea, 2022)
To carry out a factor analysis of the causes of unsatisfactory outcomes in the perinatal period in women infected with COVID-19.